Simulation and optimisation of terahertz emission from InGaAs and InP photoconductive switches - Lloyd-Hughes, J; Castro-Camus, E; Johnston, M (2005)
We simulate the terahertz emission from laterally biased InGaAs and InP using a three-dimensional carrier dynamics model in order to optimise the semiconductor material. Incident pump-pulse parameters of current Ti:Sapphire and Er:fibre lasers are chosen, and the simulation models the semiconductor's bandstructure using parabolic Γ, L and X valleys, and heavy holes. The emitted terahertz radiation is propagated within the semiconductor and into free space using a model based on the Drude-Lorentz dielectric function. As the InGaAs alloy approaches InAs an increase in the emitted power is observed, and this is attributed to a greater electron mobility. Additionally, low-temperature grown and ion-implanted InGaAs are modelled using a finite carrier trapping time. At sub-picosecond trapping times the terahertz bandwidth is found to increase significantly at the cost of a reduced emission power. © 2005 Elsevier Ltd. All rights reserved.